108k views
2 votes
F(x) = x ^ 2 + 6x - 4 in vertex form

User PromInc
by
4.4k points

2 Answers

1 vote

Answer:

f(x) = (x + 3)² - 13

Explanation:

The equation of a parabola in vertex form is

f(x) = a(x - h)² + k

Given

f(x) = x² + 6x - 4

Using the method of completing the square

add/subtract ( half the coefficient of the x- term )² to x² + 6x

f(x) = x² + 2(3)x + 9 - 9 - 4

f(x) = (x + 3)² - 13 ← in vertex form

User Sam Mackrill
by
5.1k points
3 votes

Answer:y=(x-6)^2-4

Explanation:

User Simone Manganelli
by
4.6k points